2000
DOI: 10.1016/s0006-3495(00)76492-7
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Functional Properties of Ryanodine Receptor Types 1 and 3 Expressed in a Myogenic Cell Line

Abstract: Of the three known ryanodine receptor (RyR) isoforms expressed in muscle, RyR1 and RyR2 have well-defined roles in contraction. However, studies on mammalian RyR3 have been difficult because of low expression levels relative to RyR1 or RyR2. Using the herpes simplex virus 1 (HSV-1) helper-free amplicon system, we expressed either RyR1 or RyR3 in 1B5 RyR-deficient myotubes. Western blot analysis revealed that RyR1- or RyR3-transduced cells expressed the appropriate RyR isoform of the correct molecular mass. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
108
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 47 publications
20
108
0
Order By: Relevance
“…The difference in sensitivity to 4-cmc-induced Ca 2+ release but not KCl-induced Ca 2+ release may reflect the different amounts of RyR1 and RyR3 expressed in EOM-derived myotubes. Such a hypothesis is compatible with previous findings (Fessenden et al, 2000;Matyash et al, 2002;Sekulic-Jablanovic et al, 2015) who showed that (a) EOM biopsies contain ∼100-times more RYR3 transcript than triceps biopsies, whereas orbicularis oculi express only ∼4-times more; (b) RyR3 have a significantly lower sensitivity to 4-cmc; and (c) in reconstituted 1B5 myotubes, RyR3 cannot form functional contacts with the DHPR and therefore would not contribute directly to the KCl-induced Ca 2+ release.…”
Section: Discussionsupporting
confidence: 91%
“…The difference in sensitivity to 4-cmc-induced Ca 2+ release but not KCl-induced Ca 2+ release may reflect the different amounts of RyR1 and RyR3 expressed in EOM-derived myotubes. Such a hypothesis is compatible with previous findings (Fessenden et al, 2000;Matyash et al, 2002;Sekulic-Jablanovic et al, 2015) who showed that (a) EOM biopsies contain ∼100-times more RYR3 transcript than triceps biopsies, whereas orbicularis oculi express only ∼4-times more; (b) RyR3 have a significantly lower sensitivity to 4-cmc; and (c) in reconstituted 1B5 myotubes, RyR3 cannot form functional contacts with the DHPR and therefore would not contribute directly to the KCl-induced Ca 2+ release.…”
Section: Discussionsupporting
confidence: 91%
“…Regardless of whether RyR3 and RyR1 are totally segregated, as we have suggested, or partly mixed in the junction, the activation of RyR3 is necessarily indirect, because RyR3 is not capable of being activated by skeletal DHPR (20). Thus, it is expected that RyR3 activation is a secondary event in e-c coupling, and that it follows the primary activation of RyR1 by DHPR (34), resulting in its amplification.…”
Section: Discussionmentioning
confidence: 67%
“…Muscles developing in the absence of RyR1 as a result of a lethal genetic mutation show strong developmental defects and lack of e-c coupling, despite the presence of RyR3 (18,19). Even when expressed at high levels, RyR3 alone does not induce restoration of e-c coupling (20) and tetrad formation by DHPRs (17). RyR3 seems to play a minor role in e-c coupling of mouse skeletal muscle, because changes resulting from an engineered RyR 1 null mutation are subtle (16,21).…”
mentioning
confidence: 99%
“…1A. Indeed, at 5-10μM Ca 2+ , WT RyR3 was shown to exhibit increased subconductance behavior relative to WT RyR1 [28] and [33]. This correlation is additionally supported by increased subconductance behavior of brain WT RyRs at specific Ca 2+ and ATP concentrations [34].…”
Section: Mg 2+ Inhibitionmentioning
confidence: 80%